Clinical and laboratory features of female Gitelman syndrome and the pregnancy outcomes in a Chinese cohort. Issue 10 (9th July 2020) - Zhang, Lei; Peng, Xiaoyan; Zhao, Bingbin; Zhu, Zhifeng; Wang, Ying; Tian, Dongli; Yan, Zhaoli; Yao, Li; Liu, Juntao; Qiu, Ling; Xing, Xiaoping; Chen, Limeng
Abstract: Aim: Gitelman syndrome (GS) is a rare inherited salt‐losing renal tubulopathy. Data on clinical features and the pregnancy outcome for female GS patients in a large cohort are lacking. The study was aimed to explore the phenotype and pregnant issue for female GS patients. Methods: GS cases from the National Rare Diseases Registry System of China (NRSC) were collected, and detailed clinical, laboratory and genetic data were analysed. Articles on pregnancy in GS were also systemically reviewed. Results: A total of 101 GS patients were included; among them, 42.6% were female and 79.2% showed hypomagnesaemia. A lower proportion of female patients presented before 18 years of age, with less frequently reported polyuria, higher serum potassium and less urine sodium and chloride excretions. There was no gender difference in the sodium‐chloride cotransporter (NCC) dysfunction evaluated by hydrochlorothiazide test. Twelve of the 43 female GS patients delivered after disease symptom onset, and their pregnancies were generally uneventful. As a group, pregnant GS patients had lower potassium levels in the first‐trimester ( P = .002) requiring higher potassium supplementation. After delivery, serum potassium ( P = .02) and magnesium ( P = .03) increased significantly. Both caesarean section and vaginal delivery were safe. Conclusion: Female GS patients may have a less severe phenotype with generally favourable outcomes of pregnancy. Intensive monitoring and increased potassium supplementation are necessary during pregnancy, especially in the first‐trimester. SUMMARY AT A GLANCE: This large cohort study in Chinese investigated clinical and laboratory features of female Gitelman syndrome (GS) and pregnancy outcomes. Female GS patients may have a less severe phenotype, and most pregnant patients with GS had generally favourable pregnancy outcomes.